Estudo de um laser à fibra dopada com Érbio em regime de acoplamento passivo de modos com o uso de nanotubos de carbono como absorvedores saturáveis - Rosa, Henrique Guimarães (2010)
In this work we present a study about ultrashort pulse-train generation in Erbiumdoped fiber lasers, by the passive mode-locking technique, with the use of carbon nanotubes saturable absorbers. Carbon nanotubes were incorporated into laser cavities by two techniques: thermophoresis optically-driven deposition and thin films incorporating carbon nanotubes. The second technique has become more advantageous than the first one, because is possible to control carbon nanotubes concentration and thin films thicknesses. Additionally, we present a study about thin films incorporating carbon nanotubes optimization, in order to maximize generated output bandwidths in passively mode-locked Erbium-doped fiber lasers. We used 0.8 and 1.0 nm diameters carbon nanotubes, fabricated thin films with different transmission values (different αL product values), laser cavities with different features, such as total cavity length, total accumulated dispersion, repetition rate. In this context, best results were achieved with thin films containing 1.0 nm diameter carbon nanotubes, with films transmission about 37% (αL product close to 1.0), in 9 m long laser cavity (0.8 m of highly- Erbium-doped fiber and 8.2 m of SMF) of total accumulated dispersion of 0.153 ps/nm. The largest bandwidth measured, with those characteristics cavity parameters, was 5,7 nm.